How Radar Sensors Significantly Improve the Energy Efficiency of the Smart Home - Pele Anne Francoise (Ee Times Europe, 2022)
Health-Tech-Startup Challenges, Nuclear Fusion: Promising Energy Source, Europe to Lead Quantum Revolution, EE Times 50th Anniversary.